The impact of Philippines' conditional cash transfer program on consumption - Tutor, Melba V. (2014)
The Pantawid Pamilyang Pilipino Program provides cash grants to poor households qualified on predetermined investments in human capital. This study analyses the program’s impact on consumption using the 2011 Annual Poverty Indicators Survey. Average treatment effect on the treated (ATT) is estimated through propensity score matching methodology. Heterogeneous impacts are examined among the bottom 20 percent of income distribution.

The study finds that among the total sample, per capita total expenditures is not affected by the program. In terms of monthly per capita, only carbohydrates and clothing significantly increased. As expenditure shares, education and clothing registered significant positive impact. No impact is observed on health spending, both in per capita terms and as a share of expenditure. The impact of Pantawid Pamilya on consumption is more pronounced among the poorest-fifth of households.

Results show that households have responded to program conditionalities but there is very little room to improve consumption of other basic needs. The recent program modification of increasing education grants to older children and extending support up to secondary school completion will help households sustain induced behavioral changes over time. The stronger impact on the poorest-fifth of households underscores the need to improve the targeting mechanism to address leakage issues.
Keywords: Conditional cash transfer programs; Transfer payments; Pantawid Pamilya Pilipino Program